Urgensi Partisipasi Masyarakat terhadap Izin Usaha Pertambangan Pasir - Samad, Rezki Purnama; Wahid, A. M. Yunus; Halim, Hamzah (Al-Ishlah: Jurnal Ilmiah Hukum, 2021)
This study aims to understand the essence of community participation in various stages of a sand mining business permit in Sidenreng Rappang Regency. This research was conducted using an empirical legal research method with data collection techniques through interviews, documentation studies, and data recording directly related to the research problem. The results of this study indicate that community participation in various stages of sand mining business licensing in Sidenreng Rappang Regency consists of determining the Mining Area as a requirement for preparing the Mining Business Permit Area, Regional Spatial Planning, and submitting and issuing environmental permits. The community participation related to their involvement in the issuance of mining business permits is considered not to have been effective as based on Law No. 3 of 2020, Law No. 32 of 2009, Government Regulations No. 8 of 2018, Government Regulations No. 22 of 2021, Regulation of the Minister of State Environment No. 17 of 2012, as well as related laws and regulations. Therefore, the Regional Government of Sidenreng Rappang Regency must be proactive in involving the local community, especially environmental impact analysis or environmental management efforts and environmental monitoring efforts. In addition, it is hoped that the Regional Government of Sidenreng Rappang Regency will re-identify the completeness of the mining business license requirements for mining business actors when they want to extend the mining business permits of the related companies.